2007
DOI: 10.1111/j.1440-1746.2006.04609.x
|View full text |Cite
|
Sign up to set email alerts
|

Adefovir dipivoxil therapy in liver transplant recipients for recurrence of hepatitis B virus infection despite lamivudine plus hepatitis B immunoglobulin prophylaxis

Abstract: Adefovir dipivoxil is a safe, effective treatment option for post-transplant HBV recurrence even among patients with fibrosing cholestatic hepatitis caused by lamivudine-resistant HBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…In particular, recent studies of combination lamivudine and adefovir therapy have shown lower rates of virologic breakthrough and improved biochemical response marked by lower HBV DNA, as compared to adefovir monotherapy (20). Additionally, the utility of a combination of nucleoside and a nucleotide agent is demonstrated in patients who develop HBV recurrence despite HBIg and lamivudine therapy with subsequent viral suppression after adefovir and lamivudine treatment (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent studies of combination lamivudine and adefovir therapy have shown lower rates of virologic breakthrough and improved biochemical response marked by lower HBV DNA, as compared to adefovir monotherapy (20). Additionally, the utility of a combination of nucleoside and a nucleotide agent is demonstrated in patients who develop HBV recurrence despite HBIg and lamivudine therapy with subsequent viral suppression after adefovir and lamivudine treatment (14).…”
Section: Discussionmentioning
confidence: 99%
“…patients on HBIg therapy (14,15). The use of a combination of oral drugs would result in potential cost savings of greater than $14 000 over 10 years, as compared to the standard regimens of HBIg with lamivudine (16,17).…”
Section: Saab Et Almentioning
confidence: 99%
“…The administration of low dose intramuscular (IM) HBIg has been discussed as an accepted alternative route to IV administration in several studies worldwide (Table 1) (2,3,14,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). However, given the limited volumes that can be given per IM injection, only patients with low HBIg requirements are suited for IM HBIg administration (9,53).…”
Section: Intramuscular Routementioning
confidence: 99%
“…Further, combination therapy is more cost effective because the dosage of HBIg, which is expensive, can be reduced, making NA and HBIg combination therapy far more economically attractive and potentially more widely available (17,19,40,43,44,(72)(73)(74)(75)(76). Some stud- (Table 1) (25,39,67). However, combination protocols differ amongst transplantation centers and, to some extent, the reported results have been limited by small sample sizes and short-term follow-up.…”
Section: Combination Treatment Of Nas With Hbigmentioning
confidence: 99%
“…The use of hepatitis B immune globulin (HBIG) in combination with lamivudine has dramatically improved the outcome of HBV-related transplantation [7][8][9][10][11] . The availability of newer antivirals, such as adefovir, tenofovir and entecavir, alone or in combination, offers alternative treatment options, especially in patients with lamivudine resistance [12][13][14] . Additionally, overall patient survival has improved due to the prevention of disease progression to cirrhosis.…”
Section: Introductionmentioning
confidence: 99%